Regulatory Bottlenecks of Wireless Expansion of Internet in India - Bhavya Omkarappa; Jaume Benseny; Heikki Hämmäinen (International Telecommunications Society (ITS), 2018)
The Indian telecommunication market is second largest in the world and is growing rapidly. The government is taking several measures such as National optical fiber network (NOFN) project, public WiFi pilot to bridge the gap of digital divide in order to provide Internet services throughout the country including under reserved regions of India. However, the available licensed spectrum might not be sufficient to fulfill the demand alone given the fact that it is a limited resource and its assignment to operators is highly regulated. Nevertheless, the unlicensed spectrum might be underutilized since it has around 31000 hotspots throughout the country. Community networks is an emerging concept in India, which plays an important role in bridging digital divide by exploiting unlicensed spectrum. The focus of this paper is to examine the availability of licensed spectrum and discuss the need of regulatory support to enable the growth of community networks in India. The paper studies the following hypotheses as the regulatory bottlenecks in the wireless expansion of Internet in India. i) Licensed spectrum is scarce ii) Low spectrum holdings of operators iii) Inadequate market concentration iv) Lack of regulatory incentives for community networks. The results confirm that competition act as a catalyst in the diffusion of Internet and also that the spectrum scarcity is relatively observed in local service areas in the telecom market. Since the diffusion of wireless networks is less in rural regions, support from regulatory bodies is primarily needed to improve it. Hence, we present few regulatory recommendations related to innovative licensing, and engagement of communities to support the growth of community network operators.
Keywords: 330; spectrum availability; community network operators; regulatory bottlenecks